Creativity in Teaching Teachers in the Department of Office Administration Automation at SMK Nurul Qalam Makassar - Saleh, Sirajuddin; Emiliani, Rika; Nasrullah, Muh.; Arhas, Sitti Hardiyanti; Takdir, Muhammad (Jurnal Office, 2021)
Teachers' teaching creativity relates to designing and preparing teaching materials/subject materials, managing classes, using varied methods, utilizing media, to developing evaluation instruments. This study aims to determine the creativity of teaching teachers in the Office Administration Automation Department  at SMK Nurul Qalam Makassar. To find out these objectives, the researchers used a qualitative descriptive type of research. The informants in this study were 7 people using data collection techniques that were carried out through observation, interviews, and documentation. The data obtained from the research results were processed using data analysis techniques consisting of data collection, data condensation, data presentation, conclusions, and withdrawal/verification. The results showed that the creativity of teaching teachers in the Office Administration Automation Department at SMK Nurul Qalam Makassar was in the Effective category. Judging from the aspect of formulating learning objectives well, Having companion books for students, Choosing learning methods, Creating/using teaching aids media.